2016
DOI: 10.3233/npm-16915034
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue factor and thrombomodulin expression and histopathological changes in placentas of pregnancies with preeclampsia

Abstract: In placenta of patients with preeclampsia, we detected abnormal expression of F3 and THBD with increased protein and mRNA levels. The role of these molecules in the pathogenesis of this disease and in alterations of hemostatic and histopathological aspects of placentas need further studying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, no consensus has been reached on THBD expression or activity in placentas of pregnancies affected by PE. Neither Kanfer et al nor López‐Ramírez et al found significant differences in activity or protein levels between cases and controls, respectively 18,23 ; Bosco et al found reduced THBD levels in vascular villi and increased levels in perivascular and stromal myofibroblasts but no differences in syncytiotrophoblasts 20 ; Turner et al and Zhu et al found diminished levels of THBD protein and mRNA 17,32 ; and our group in a previous study found increased THBD mRNA and protein levels, measured by qRT‐PCR and ELISA, in placentas of pregnancies complicated by PE 19 . Inconsistent findings could be due to differences in case and control inclusion criteria, sample collection sites or methodology.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, no consensus has been reached on THBD expression or activity in placentas of pregnancies affected by PE. Neither Kanfer et al nor López‐Ramírez et al found significant differences in activity or protein levels between cases and controls, respectively 18,23 ; Bosco et al found reduced THBD levels in vascular villi and increased levels in perivascular and stromal myofibroblasts but no differences in syncytiotrophoblasts 20 ; Turner et al and Zhu et al found diminished levels of THBD protein and mRNA 17,32 ; and our group in a previous study found increased THBD mRNA and protein levels, measured by qRT‐PCR and ELISA, in placentas of pregnancies complicated by PE 19 . Inconsistent findings could be due to differences in case and control inclusion criteria, sample collection sites or methodology.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, studies have reported increased F3 levels in PE placentas with abnormalities confirmed by Doppler velocimetry 27 . Our group discovered an increase in placental F3 and THBD mRNA and protein levels with a high frequency of decidual arteriopathy, acute infarction, and syncytial knots in placentas with PE 19 . Recently, Liu et al described an F3 increase in PE placentas and plasma, concurrent with reduced gene promoter methylation 28 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This plays an important role in promoting neo‐angiogenesis, thereby facilitating selective expansion of vascular endothelial cells and increasing blood flow 15 . THBD, an endothelial‐specific type I membrane receptor that binds thrombin, is encoded by an intron‐less gene and exerts a natural anticoagulant effect by changing the substrate specificity of thrombin 16 . THBS2, a member of the thrombospondin family, inhibits angiogenesis by directly affecting endothelial cell migration, proliferation, survival, and apoptosis, and antagonizing VEGF activity 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the blood TM levels remained constant from nonpregnant women to normotensive pregnant women, it was higher in early severe preeclampsia women to late severe preeclampsia groups, 16 and it increased significantly from normotensive pregnant to mild pre‐eclampsia to severe pre‐eclampsia 11 . In placenta of patients with preeclampsia, TM levels was higher than pregnant women without pregnancy complications 17 . TM levels were significantly higher in patients who experienced episodes of DVT compared to healthy individuals 12 .…”
Section: Introductionmentioning
confidence: 86%